Strength and Fatigue Properties of Sandstone under Dynamic Cyclic Loading - Mingming He; Ning Li; Yunsheng Chen; Caihui Zhu (Shock and Vibration)
This paper presents an experimental investigation of strength and fatigue properties of intact sandstone samples subjected to dynamic cyclic loading in the laboratory. Tests were conducted on sandstone samples with loading frequencies ranging in 0.5, 1, 2, and 4 Hz, loading amplitudes of 1, 15, 30, 60, 90, and 120 kN, and loading speeds of 0.5, 1, 2, 4, and 8 kN/s. In this study it was shown that the loading frequency, as well as the amplitude and loading speed, was of great significance and affected the mechanical characteristics of sandstone under dynamic cyclic loading. The fatigue life of sandstone was found to decrease with loading speeds and amplitudes but increase with loading frequencies. It was found that the minimum of the dynamic strength and deformation factor of sandstone was obtained at loading speeds of 2 kN/s but the maximum at loading frequencies of 1 Hz. Finally, it was concluded that the relationship between the fatigue life and loading speed, frequency, and stress amplitude under dynamic cyclic loading would be expressed as the S-N curve, which showed that the fatigue characteristic of sandstone was similar to that of metal materials.